Modeling health signals of the COVID-19 pandemic in Iraq using non-standard modified maps (مجلة جامعة سرت للعلوم الانسانية, 2022)
In its structure the study seeks to treat some of the problems of thematic maps that do not perform their visual purpose as required. Therefore this study came to represent the health indicators (COVID-19) using non-standard modified maps (cartogram) in an attempt to treat the visual perception problems facing the map reader by focusing on showing the objective of the map. The cartographic modeling used for health indicators showed the effectiveness of this type of maps in highlighting the spatial discrepancies in indicators of injury recovery and death between administrative units in a way through which the reader can obtain a conceptual understanding and a more discerning scientific view of the statistical values ​​used in this study
Keywords: corona pandemic; modified maps; map design; quantitative signals; oftware